Synthesis And Cytotoxicity Evaluation Of Diarylpyrazine And Dihydropyrazine Derivatives - PARISA MIRALINAGHI; MONA SALIMI; SARA SHIRMOHAMMADLI; MOHSEN AMINI (International Journal of Pharma and Bio Sciences, 2011)
Some 2,3-diaryl pyrazines and 5,6-diaryl-2,3-dihydropyrazine were synthesized and evaluated for their cytotoxicity study. 2,3-Diarylpyrazines were prepared from oxidation of 5,6-diarly-2,3-dihydropyrazine by sulfur. The synthesized compounds were tested for their cytotoxicity effects toward (MT-29) cancer cell line using MTT-assay. The results showed compounds 4a and 4b were two most active compounds.